Health professionals' overestimation of knowledge on snakebite management, a threat to the survival of snakebite victims-A cross-sectional study in Ghana. - Evans Paul Kwame Ameade; Isaac Bonney; Evans Twumasi Boateng (Public Library of Science (PLoS), 2021)
Background According to the World Health Organization, snakebites, a common occupational hazard in developing countries accounts for an annual loss of between 81,000 and 138, 000 lives following 5 million bites of which 2.7 million results in envenomation. Since snakebite-associated morbidity and mortality are more prevalent in agricultural economies such as Ghana, health professionals should be optimally knowledgeable on how to manage the incidence of snakebites. Lack of knowledge or overestimation of a professional's knowledge can affect heath delivery especially for emergencies such as snakebites. The three rurally situated Tongu districts in South-Eastern Ghana with agriculture as the major source of livelihood for their inhabitants, are prone to snakebites. This study, therefore, brings up the need to assess whether the health professionals in these districts are well-equipped knowledge-wise to handle such emergencies and whether they can rightly estimate their knowledge with regards to snakebite management. Methodology/principal findings Data was collected using a de novo semi-structured questionnaire administered through google form whose link was sent via WhatsApp to 186 health workers made up of nurses, midwives, physician assistants, medical doctors, pharmacists, and pharmacy technicians. This data was analyzed using Statistical Package for the Social Sciences (SPSS) Version 25. Association between variables was determined using the appropriate tools where necessary, using a confidence interval of 95% and significance assumed when p ≤ 0.05. This study found male health workers significantly more knowledgeable about snakebite management (11.53±5.67 vs 9.64±5.46; p = 0.022) but it was the females who overestimated their knowledge level (27.9% vs 24.1%). The medical doctors exhibited the best knowledge on snakebite management with the registered general nurses least knowledgeable. Although most professionals overestimated their knowledge, the registered general nurses were the worst at that (53.7%). Overall knowledge of health care professionals on snakebite management was below average [10.60±5.62/22 (48.2%)] but previous in-service training and involvement in the management of snakebite were associated with better knowledge. Respondents who had no previous training overestimated their knowledge level compared to those who had some post-qualification training on snakebite management (38.1% vs 7.5%). The greatest knowledge deficit of respondents was on the management of ASV associated adverse reactions. Conclusion Health workers in rural Ghana overestimated their knowledge about snakebite management although their knowledge was low. Training schools, therefore, need to incorporate snakebite management in their curriculum and health authorities should also expose health workers to more in-service training on this neglected tropical disease.